Efektivitas Edukasi Menyikat Gigi Menggunakan Media Video Animasi Terhadap Pengetahuan Kesehatan Gigi dan Mulut Pada Anak Sekolah Dasar - Jumriani, Jumriani; Liasari, Ira; Priyambodo, R. Ardian; Putri. M, Aisca (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Oral and dental health is an important aspect of overall health, especially in children. However, many children still have limited knowledge and poor dental health behaviors. Dental health education, particularly toothbrushing education using animated video media, is needed to improve children’s knowledge and dental health practices. This study aims to determine the effectiveness of toothbrushing education using animated video media on the oral health knowledge of elementary school students. The method used was quantitative research with a pre-experimental design in the form of a pretest–posttest group design. The study population consisted of 418 students from SDN 62 Palisi, Maros Regency, with 120 samples selected through stratified random sampling representing grades 1–6. Data were analyzed using SPSS 20 with univariate and bivariate tests, including the Kolmogorov–Smirnov normality test, t-test, or Wilcoxon test. The results showed that toothbrushing education using animated video media was effective in improving students’ oral health knowledge, with a p-value of <0.001, indicating statistical significance at p < 0.05. The study concludes that animated video-based toothbrushing education is effective in increasing students’ knowledge. It is recommended that schools utilize animated videos in learning activities or extracurricular programs. The animated videos produced are expected to be used by teachers as learning tools and as promotional media to enhance knowledge on maintaining oral and dental health.